The Role of Islamic Banks' Financial Performance on Corporate Social Responsibility (CSR) - Nurdyanzah, Muh; Junaidi, Junaidi; Sultan, Sultan (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
This study aims to obtain empirical evidence of factors that can affect the CSR performance of the Islamic social reporting (ISR) index of Islamic banks, which then interact with moderating variables. The method used is a quantitative method with multiple regression techniques and moderated regression analysis used to analyze the data. The factor used is Islamic social reporting, and the moderating variable is financial performance contained in the annual reports of several Islamic banks in Indonesia. From 2012 to 2021, the population of this study is Indonesian Islamic Commercial Banks (BUS). The sample obtained based on the sample selection criteria is only four Islamic commercial banks with a total of only 40 observations, indicating that the sample is still relatively small and the resulting value is relatively low to explain the company's financial performance. The time series method is used to process the data. The result show ROA and ROE can moderate and strengthen the impact of ISR on firm performance, ISR has a favorable and considerable impact on the financial performance of Islamic banks. The added value of the company is supported theoretically and empirically by this study. For this research to be used as a reference to explain phenomena with existing theories, the hypotheses made are stated descriptively and then accompanied by a Sharia perspective.